Resolved epilepsy: an updated insight - S. A. Gromov; N. A. Sivakova (Эпилепсия и пароксизмальные состояния, 2019)
Classification of epilepsy is of great importance at the stages of rehabilitation when the disease is considered resolved. This is the time to address various aspects of etiology, pathogenesis, compensation and resolution of epilepsy and to decide upon further medical care. Materials and methods. Here we review clinical-neurophysiological, experimentalpsychological, and neuroimaging results of anti-epileptic treatment and its discontinuation in seizure-free patients. We also discuss the adoption of the new international classification of ILAE 2017 in the domestic epileptology and analyze clinical cases of 270 patients with epilepsy who were in control of seizures for up to 8 years. Results. The study revealed the clinical, neuropsychological and neurophysiological signs of epilepsy regression in patients with long-term control of seizures. In 85% of these patients, seizures were under control; in 45% of them, the issue of “resolution of epilepsy” was a matter of discussion. In this regard, we address the timing and indications for the discontinuation of antiepileptic drugs. Conclusion. The prolonged absence of seizures is due to an inhibition of epileptic activity at the neuronal level with a gradual restoration of the antiepileptic system during 3-5 years of seizure-free period; this mechanism is reflected in the new classification. The data obtained in the present study support the decision of the Russian League against Epilepsy to introduce the new classification of epilepsy proposed by ILAE in 2017. The new term “resolved epilepsy” has been adopted for use in patients previously referred to as “practically recovered”.